1984
DOI: 10.1161/01.cir.69.3.468
|View full text |Cite
|
Sign up to set email alerts
|

Sodium susceptibility and potassium effects in young patients with borderline hypertension.

Abstract: To evaluate sodium susceptibility in subjects with borderline hypertension at increased risk of developing essential hypertension, the effect of salt loading after sodium deprivation with a diuretic was studied in 21 young patients with borderline hypertension and 12 age-matched normal subjects. Treatment with a diuretic caused significant decreases in mean blood pressure (MBP) in subjects with borderline hypertension but not in normotensive subjects. In borderline hypertensives, the subsequent sodium loads re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0

Year Published

1987
1987
2006
2006

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 64 publications
(20 citation statements)
references
References 41 publications
1
19
0
Order By: Relevance
“…In contrast, Gudmundsson et al 38 found no significant changes in blood pressure, forearm blood flow, or resistance among normotensive men with and without a family history of hypertension subjected to a high sodium intake, and no differences in the degree of suppression of plasma renin activity or aldosterone concentration in those genetically predisposed to become hypertensive. Fujita et al 39 observed that patients with essential hypertension had greater changes in blood pressure than did normal subjects after receiving diuretics or sodium supplements; however, plasma norepinephrine, epinephrine, and renin activity were significantly higher than those of normotensive subjects. The increase in blood pressure was due to an increase in cardiac output with an inadequate fall in total peripheral resistance.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, Gudmundsson et al 38 found no significant changes in blood pressure, forearm blood flow, or resistance among normotensive men with and without a family history of hypertension subjected to a high sodium intake, and no differences in the degree of suppression of plasma renin activity or aldosterone concentration in those genetically predisposed to become hypertensive. Fujita et al 39 observed that patients with essential hypertension had greater changes in blood pressure than did normal subjects after receiving diuretics or sodium supplements; however, plasma norepinephrine, epinephrine, and renin activity were significantly higher than those of normotensive subjects. The increase in blood pressure was due to an increase in cardiac output with an inadequate fall in total peripheral resistance.…”
Section: Discussionmentioning
confidence: 99%
“…18,19 Therefore, it is a plausible hypothesis that potassium supplementation could attenuate salt retention during the high-salt diet period in DS rats, possibly through the natriuretic effect of potassium. [35][36][37] …”
Section: Matsui Et Al Effect Of Potassium On Cardiac Function 227mentioning
confidence: 99%
“…51 Similarly, there are data to suggest that a high potassium diet ameliorates the hypertensive response to sodium administration in salt-sensitive subjects. 42 The many published studies also indicate that we still do not know the time period during which an individual has to consume a high salt diet before sodium sensitivity is apparent. If individuals followed one of the reported protocols for 1 month, 6 months, or 1 year, would more salt sensitivity be evident?…”
Section: Human Studiesmentioning
confidence: 99%